Kontribusi Kompetensi Dignostik dan Komunikasi Interpersonal Pelayanan Pastoral terhadap Sikap Beriman Kaum Muda dalam Gereja - Gerbin Tamba; Donald Loffie Muntu; Joseph H. Sianipar (PT. Penerbit Tiga Mutiara, 2025)
The pastor plays various important roles in the congregation, such as preacher, teacher, priest, administrator, and counselor. Among all these roles, the counselor holds the greatest responsibility. The task of pastoral counseling includes providing emotional and spiritual support to the congregation. In addition to helping the congregation overcome emotional, mental, and spiritual issues, counseling also assists them in discovering their identity, life calling, and potential, so that they can develop holistically in life. Pastoral counseling is a form of interpersonal communication that requires the pastor to have good communication skills. The ability to build strong relationships with the congregation significantly influences their spiritual development. Additionally, empathy and compassion are qualities that pastors must possess to support their interpersonal skills. Diagnostic skills are also crucial for a pastoral counselor. With these skills, the counselor can identify the problems faced by the congregation and provide assistance or refer them for further treatment. Interpersonal skills help build open relationships, while diagnostic abilities are essential in identifying the root causes of the congregation's issues. In the diagnostic process, assessment and interpretation skills are vital to understanding the congregation's problems comprehensively—emotionally, mentally, socially, culturally, and spiritually—so that the solutions provided can be effective and accurate. Pastoral counseling plays a significant role in supporting the growth of faith and overall well-being of the congregation.